The Dance of the Ghosts: A New Cold War with Russia Will Not Serve Western Interests. Issue 5 (3rd September 2018) - Lieven, Anatol
Abstract : In their nostalgia for the Cold War, Western elites may be trying to revive the comforting ghosts of the past to cope with a frightening present.